ANALYSIS OF INVENTORY AND RAW MATERIAL COST VALUATION USING FIFO, LIFO AND WEIGHTED AVERAGE METHODS - Maria Lapriska Dian Ela Revita; Jumiyati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Statement of Financial Accounting Standards (PSAK) No. 14 explains inventory issues, including inventory valuation, methods used to record inventory, and inventory reporting. This study aims to calculate the valuation of raw material costs and the value of ending inventory of raw materials using the FIFO, LIFO, and Weighted Average methods. In this paper, the author uses a descriptive qualitative method and Literature Study. Based on the results of the calculation of the three methods in the Case Study of PT. "Perdana Paskalis" in April 2026, it shows that the cost of raw material usage is 5,000 kg, for the lowest value is indicated by using the FIFO method. Valuation using the LIFO method is 6.5% higher, while using the Average method is 20.20% higher than the FIFO method. In the calculation of raw material inventory, which is 900 kg, the LIFO method shows the largest inventory value. Valuation using FIFO is 3.06% higher, while the Average method is 1.2% higher than the LIFO method.